Advisory content in politics: the form of mitigation of the negative impact of identity politics on Instagram account @lensamu and @nuonline_id - Istiati, Fuandani; "˜Aziizah, "˜Aabidah Ummu (Journal of Social Studies (JSS), 2024)
This article aims to analyze efforts to mitigate the negative impacts of identity politics by two large mass organizations in Indonesia, Muhammadiyah and Nahdhatul Ulama (NU), through their Instagram accounts. Mitigation in this context refers to steps to recognize and increase awareness of identity politics risks often occurring in campaigns, especially before the 2024 election. This research is motivated by the political situation leading up to the 2024 election and vulnerability to identity politics, which perpetrators often use as a tool. The method used in this research is quantitative content analysis with content research objects discussing political themes and the 2024 election. Data was collected through virtual observation, literature research, and online documentation via the Instagram accounts @lensamu and @nuonline_id from September 2023 to February 2024. Based on the research results, it can be concluded that the percentage of forms of mitigating the negative impact of identity politics carried out by the @lensamu account is 0.91 or 91% and by @nu_online it is 0.86 or 86%. With these test results, it can be said that the form of mitigation of the negative impact of identity politics carried out by these two accounts is high in facing the 2024 election.